Do circular economy practices affect corporate performance? Evidence from Italian large‐sized manufacturing firms. (27th May 2022) - Mazzucchelli, Alice; Chierici, Roberto; Del Giudice, Manlio; Bua, Ilenia
Abstract: In recent years, corporate social responsibility has become the most outstanding challenges for firms and circular economy has emerged as an innovative business model able to transform corporate social responsibility into actions. Even if by adopting such a strategic model firms could enhance their performance, results continue to be mixed and unclear. The aim of the paper is twofold. First, the study investigates the effect of three circular economy practices (waste treatment, reduction and recycling), on brand reputation and financial performance. Second, the study tests the role of brand reputation in mediating the relationship between circular economy practices and financial performance. The findings highlight the crucial role of 3Rs practices and of brand reputation in enhancing firm performance. This paper contributes to a better understanding on the relationship between circular economy practices, as sustainable strategic and managerial practices, and firm performance, in both marketing and financial terms. Moreover, it sheds light on circular economy implementation and its effect at the firm level, by analyzing managers perceptions on how firms and policy makers have to incorporate the circular economy concept in their sustainability agenda.